I am Anne Frank - Meltzer, Brad.; Eliopoulos, Chris (New York : Dial Books for Young Readers, 2020)
An illustrated biography of the life of Anne Frank, a Jewish girl who hid from the Nazis in World War II and became famous for her diary.
Includes bibliographical references.
2.6
K-3.
K-3
Keywords: Frank, Anne, -- 1929-1945 -- Juvenile literature; Frank, Anne, -- 1929-1945.; Frank, Anne, -- 1929-1945.; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Juvenile literature; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Juvenile literature; Jews -- Netherlands -- Amsterdam -- Biography -- Juvenile literature; Holocaust, Jewish (1939-1945); Jews -- Biography; Women; Holocaust, 1939-1945.; Jews -- Biography; Women -- Biography; Biographies; Picture books